The ARIMA Box-Jenkins Method has been used to Predict the Price of Large Curly Red Chilis - Yustirania Septiani; Vinca Ayu Setyowati (Gorontalo Development Review, 2021)
Chili is one of the potential commodities based on market demand and high economic value. The price of chili has fluctuated every month so that this commodity contributes to inflation in food that can affect overall general inflation. Thus, an analysis of forecasting prices for large curly red chili is needed so thar people and farmers do not need to worry and can prepare for future risks. Price forecasting in this study uses the Box-Jenkins ARIMA method. The data used is the price of lare curly red chili prices from December 2015 to April 2020. The data to be analyzed is then made into several forms of the ARIMA model and one will be chosen as the best ARIMA model. Based on the results of the study, ARIMA (1,1,3) is the best model. Thus the forecast results obtained for the price of large curly red chili in Magelang City from May 2020 to February 2021. With this research it is expected ti be able to assist the Depasrtment of Industry and Trade of Magelang City in making decisions related to the price of lare curly red chilli which fluctuates every year.